The Strong Fe K Line and Spin of the Black Hole X-Ray Binary MAXI J1631-479 - Zdziarski, Andrzej A.; Chand, Swadesh; Dewangan, Gulab; Misra, Ranjeev; Szanecki, Michal; You, Bei; Parra, Maxime; Marcel, Grégoire (Institute of Physics Publishing, 2026)
We study the transient black hole binary MAXI J1631–479 observed simultaneously by NICER and NuSTAR in its soft spectral state. Its puzzling feature is the presence of a strong and broad Fe K line, while the continuum includes a prominent disk blackbody and a very weak power-law tail. The irradiation of the disk by a power-law spectrum fitting the tail is far too weak to explain the strong line. Previous proposals included the idea that the Fe K emission is intrinsic to the disk. Here, we propose that the strong line can be explained by the irradiation of the disk by photons from Comptonization of the disk blackbody by coronal electrons. One crucial effect is that the shape of the irradiating spectrum at ≲10 keV reflects that of the disk blackbody; it is strongly curved and has a higher flux than what would be produced by a fit with a power-law irradiation. The other effect is a relativistic enhancement of the backscattered coronal flux incident on the disk. Both effects together can account for the line, although the latter is modeled only quantitatively. While this result is independent of the physical model used for disk emission, the fitted spin depends heavily on that model. When employing a Kerr disk model for a thin disk with color correction, the fitted spin appears retrograde, rare for a Roche-lobe overflow binary. A model that accounts for both the finite thickness of the disk and radiative transfer yields a spin of a* ≈ 0.8–0.9.